TINGKAT EFIKASI DIRI DALAM MENYUSUN SKRIPSI PADA MAHASISWA BIMBINGAN DAN KONSELING UNIVERSITAS MUHAMMADIYAH PROF. DR. HAMKA ANGKATAN 2018 - Nisa Afina Hasya; Chandra Dewi Sukma (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The purpose of the study is to find out and describe the level of self-efficacy in compiling a thesis for Guidance and Counseling students of the University of Muhammadiyah Prof. DR. HAMKA Class of 2018. Research methods are quantitative methods with a quantitative descriptive type of research. The study population was 169 people. The sample was 157 people. The sampling technique uses saturated samples. The validity test yielded 45 items out of 50 items using the person product moment. Reliability calculation using Alpha Cronbach using IBM SPSS 2.5 with research results of rac 0.949 > 0.6 is reliable. The results of the research conducted on the level of self-efficacy in Guidance and Counseling students of the University of Muhammadiyah Prof. DR. HAMKA class of 2018 obtained a score of 22136 which was at a high categorization level. The results of the study from respondents, as many as 58 students had a very high self-efficacy rate of 37%, 86 students had a high self-efficacy rate of 55%, 10 students had a moderate self-efficacy rate of 6%, 3 students had a low self-efficacy rate of 2%